Edukasi dan Pelatihan Puding Daun Kelor untuk Pencegahan Stunting di Dusun Kedungsogo, Kulon Progo - Kusumawardhani, Ratih; Prihatin, Wijiasih; Hartono, Arif (Penerbit Goodwood, 2025)
Purpose: This community service aims to provide understanding and skills to the community, especially PKK Kedungsogo, Kulon Progo women, about the benefits of Maringa leaves in preventing stunting in children Methodology: This activity included a presentation about the benefits and nutritional content of Moringa leaves and training in making Moringa leaf pudding as an alternative nutritious food. Using a mixed-method approach, the results of the community service showed an increase in the PKK women's understanding of the benefits of Moringa leaves for stunting prevention. Results: The activity results show the enthusiasm of PKK women for processing Moringa leaves as a step to prevent stunting and as a solution for other health needs. This initiative increases their nutrition knowledge and opens up new opportunities for utilizing local resources to improve children's health. PKK mothers' understanding of the importance of the benefits of Moringa leaves for preventing stunting is also increasing. Conclusions: PKK moms in kedungsogo hamlet were the target of socialization and training sessions on the use of moringa leaves, and the events were a great success and had good feedback. Through the development of moringa leaf-based products and the enchancement of mothers abilities to include moringa leaves into family meals this intiative is anticipated to help prevent childhood stunting. Limitations: The initial level of public knowledge about Moringa leaves and stunting can vary. Some community members may not be familiar with the benefits of Moringa leaves or the concept of stunting, so effectively conveying information requires additional time and effort. Contribution: Socialization and training about the benefits of Moringa leaves are essential to increasing public knowledge about their use. This increase in knowledge may motivate families to adopt moringa leaves as part of a healthy diet for their children